Somatic Mosaicism for a "Lethal" GJB2 Mutation Results in a Patterned Form of Spiny Hyperkeratosis without Eccrine Involvement. Issue 3 (18th April 2016) - Eskin‐Schwartz, Marina; Metzger, Yoav; Peled, Alon; Weissglas‐Volkov, Daphna; Malchin, Natalia; Gat, Andrea; Vodo, Dan; Mevorah, Baruch; Shomron, Noam; Sprecher, Eli; Sarig, Ofer
Abstract: Background: Spiny hyperkeratosis refers to a rare clinical phenotype characterized by nonfollicular keratotic projections and sometimes associated with other acquired and inherited conditions. We describe a case of congenital patterned spiny hyperkeratosis. Methods: To identify the cause of this disorder, we used a combination of whole exome sequencing, direct sequencing and TaqMan assay. Results: We found that the peculiar clinical features displayed by the patient are due to somatic mosaicism for a heterozygous mutation in the GJB2 gene. Conclusion: Because histopathologic examination of two independent biopsies did not reveal porokeratotic eccrine ostial and dermal duct nevus (PEODDN), previously reported to result from somatic mutations in GJB2, it appears that mutations in this gene can cause nevoid spiny hyperkeratosis in the context of PEODDN or as an isolated finding.